Negative grid line silver paste of N-type IBC battery, N-type IBC battery and preparation method of N-type IBC battery

CN119132692AActive Publication Date: 2024-12-13DAS SOLAR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310700489.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

The existing N-type IBC batteries cannot form n+ zones, resulting in poor photoelectric conversion efficiency.

Method used

Silver paste containing antimony, tellurium and tungsten doped glass powder is used to form the negative gate line of the N-type IBC battery. The N-zone doping and tellurium and tungsten are increased by increasing the contact resistivity of the silver gate line and increasing the filling. Factors to improve the photoelectric conversion efficiency of the battery.

Benefits of technology

It effectively solved the problem of poor photoelectric conversion efficiency of N-type IBC batteries and improved the battery efficiency by 0.08%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119132692A_ABST
    Figure CN119132692A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an N-type IBC battery negative electrode grid line silver paste, an N-type IIBC battery and a preparation method thereof, the N-type IBC battery negative electrode grid line silver paste provided by the embodiment of the invention comprises an organic auxiliary agent, silver powder, an organic binder and doped glass powder, and the doped elements of the doped glass powder are antimony, tellurium and tungsten. The antimony, tellurium and tungsten elements are doped in the glass powder, and the antimony element and phosphorus are pentavalent elements, so that the doping of an N region can be increased; the tellurium and the tungsten have a silver dissolving effect, so that the contact resistivity of the silver grid line can be reduced, the filling factor is improved, and the photoelectric conversion efficiency of the cell is improved; therefore, the problem that the photoelectric conversion efficiency of the N-type IBC battery is poor due to the fact that an n + region cannot be formed in an existing N-type IBC battery is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to an N-type IBC cell cathode grid line silver paste, an N-type IBC cell and a preparation method thereof. Background Art

[0002] The interdigitated back contact (IBC) battery is a new type of battery in which the contact electrodes of the P / N junction, substrate and emitter region are made in an interdigitated shape on the back of the battery. Its core technology is to prepare high-quality p-regions and n-regions arranged in an interdigitated shape on the back of the battery.

[0003] At present, N-type IBC batteries use N-type original silicon wafers, and their p-regions are doped using boron diffusion superimposed on laser SE technology to form p+ doped regions, which can reduce metal recombination and increase the opening voltage. However, since the N-region cannot be doped using tubular diffusion, that is, the N+ region cannot be formed, the efficiency improvement effect of the N-type IBC battery is not good. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an N-type IBC battery negative electrode grid line silver paste, an N-type IBC battery and a preparation method thereof, so as to solve the problem that the existing N-type IBC battery cannot form an n+ region, resulting in poor photoelectric conversion efficiency of the N-type IBC battery.

[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:

[0006] The present invention provides a silver paste for negative grid lines of an N-type IBC battery, wherein the components constituting the silver paste include an organic additive, silver powder, an organic adhesive and doped glass powder, and the doping elements of the doped glass powder are antimony, tellurium and tungsten.

[0007] Furthermore, in the silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 0.8-1.5%, 76-84%, 11.3-21.2% and 2-3.2% respectively.

[0008] Furthermore, in the silver paste, the doped glass powder includes 10-25% Bi2O3, 6-8% Al2O3, 8-15% SiO2, 5-15% ZnO, 25-40% Sb2O3, 5-12% TiO2, 5-12% WO2, 5-10% MgO and 15-20% TeO3 in mass percentage.

[0009] Furthermore, in the silver paste, the D50 of the doped glass powder is 1.5 to 2 μm.

[0010] Furthermore, in the silver paste, the organic additive includes three or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate mixture.

[0011] Furthermore, in the silver paste, the organic binder includes a high molecular polymer resin and an organic solvent;

[0012] The mass fraction of the high molecular weight polymer in the organic binder is 10 to 15%;

[0013] The mass fraction of the organic solvent in the organic binder is 85-90%.

[0014] Furthermore, in the silver paste, the high molecular polymer is resin-50;

[0015] The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0016] Furthermore, in the silver paste, the silver powder includes micron-spherical silver powder and nano-spherical silver powder.

[0017] The present invention also provides a method for preparing an N-type IBC battery, which comprises:

[0018] After forming an n-type doped region and a p-type doped region arranged in an interdigitated manner on the back of an N-type silicon wafer, a passivation layer is formed on the surface of the n-type doped region and the p-type doped region;

[0019] An opening connected to the p-type doping region is formed in the first region of the passivation layer, and aluminum paste is printed at the opening, and silver paste is printed in the second region of the passivation layer; the projection of the first region is within the range of the p-type doping region, and the projection of the second region is within the range of the n-type doping region; wherein the silver paste comprises an organic additive, silver powder, an organic binder and doped glass powder, and the doping elements of the doped glass powder are antimony, tellurium and tungsten;

[0020] The N-type silicon wafer with aluminum paste printed in the opening and silver paste printed in the second area is sintered at high temperature to obtain an N-type IBC battery.

[0021] The present invention also proposes an N-type IBC battery, wherein the IBC battery is prepared by the method as described above.

[0022] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0023] In the embodiment of the present invention, the silver paste for negative gate line of N-type IBC battery provided includes organic additive, silver powder, organic binder and doped glass powder, and the doping elements of doped glass powder are antimony, tellurium and tungsten. Among them, antimony and phosphorus are both pentavalent elements, which can increase the doping of N region; while tellurium and tungsten have silver dissolving effect, which can reduce the contact resistivity of silver gate line and improve the filling factor, thereby improving the photoelectric conversion efficiency of battery; thus, it solves the problem that the existing N-type IBC battery cannot form n+ region, resulting in poor photoelectric conversion efficiency of N-type IBC battery.

[0024] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a flow chart of a method for preparing silver paste for negative electrode grid lines of an N-type IBC battery provided by an embodiment of the present invention;

[0026] Figure 2 It is a flow chart of a method for preparing an N-type IBC battery provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] The applicant of the present invention has found that the current N-type IBC battery uses N-type original silicon wafers, and its P-type region adopts boron diffusion superimposed laser SE technology to reduce metal recombination and increase the opening voltage; but the N region cannot be doped by tubular diffusion for the time being, that is, the n+ region cannot be formed, so that the efficiency of the N-type IBC battery cannot be effectively improved.

[0029] In order to solve the above problems, an embodiment of the present invention provides an N-type IBC battery negative electrode grid line silver paste, the components of the silver paste include organic additives, silver powder, organic adhesive and doped glass powder, and the doping elements of the doped glass powder are antimony, tellurium and tungsten.

[0030] The N-type IBC battery negative electrode grid line silver paste provided in the embodiment of the present invention is used to form the negative electrode grid line of the N-type IBC battery, which can be a negative electrode main grid and / or a negative electrode fine grid; wherein the back side of the above-mentioned N-type IBC battery is a P-type region formed by boron diffusion superimposed laser SE technology.

[0031] Among them, silver powder is the main component, and silver powder is mainly used to form the N-type emitter of the battery; doped glass powder is an inorganic adhesive, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role. The doping elements antimony and phosphorus are both pentavalent elements, which can increase the doping of the N zone; tellurium and tungsten have a silver-dissolving effect, which can reduce the contact resistivity of the silver grid line and increase the filling factor, thereby improving the efficiency of the battery, thus solving the problem that the existing N-type IBC battery cannot form an n+ zone, resulting in poor photoelectric conversion efficiency of the N-type IBC battery; organic binders can ensure the overall bonding effect; organic additives can reduce the overall viscosity of the silver paste.

[0032] The silver paste provided in the embodiment of the present invention can effectively form an N-type region on an N-type silicon wafer, has better contact with the battery cell itself, has smaller series resistance than traditional silver paste, and can improve the efficiency of the battery by 0.08%.

[0033] In the embodiment of the present invention, antimony, tellurium and tungsten are all added to the glass powder in the form of oxides to form the above-mentioned doped glass powder, that is, the above-mentioned doped glass powder includes antimony oxide, tellurium oxide and tungsten oxide. Optionally, the above-mentioned antimony oxide can be Sb2O3, the tellurium oxide is TeO3, and the tungsten oxide is WO2.

[0034] Alternatively, in one embodiment, the doped glass powder includes 10-25% by mass of Bi2O3, 6-8% by mass of Al2O3, 8-15% by mass of SiO2, 5-15% by mass of ZnO, 25-40% by mass of Sb2O3, 5-12% by mass of TiO2, 5-12% by mass of WO2, 5-10% by mass of MgO, and 15-20% by mass of TeO3, and the D50 of the doped glass powder is 1.5-2 μm, and if the D50 is less than 1.5 μm, the doped glass activity is too large, and if the D50 is greater than 2 μm, the doped glass activity is too small. Optionally, the D50 of the glass powder is 1.6-1.8 μm.

[0035] Among them, Bi2O3 is the main network structure; Al2O3 can adjust the glass stability and increase the viscosity; SiO2, as a glass network former, promotes glass stability and lowers the glass melting point; ZnO can break the network structure and promote glass crystallization; Sb2O3 is used for N-type doping to achieve an N-zone doping effect similar to phosphorus; TiO2 is used for local crystallization; MgO is used to lower the melting point; WO2 is used to dissolve larger particles of silver powder, while TeO3 is used to dissolve smaller particles of silver powder, and can perform local microcrystals and lower the melting point.

[0036] Optionally, in one embodiment, in the above silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 0.8-1.5%, 76-84%, 11.3-21.2% and 2-3.2%, respectively.

[0037] Optionally, in one embodiment, in the above silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 1-1.2%, 78-82%, 15-18% and 2.5-3%, respectively.

[0038] For example, in the silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 0.8%, 84%, 12% and 3.2% respectively.

[0039] For example, in the silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 1.5%, 76%, 20.5% and 2% respectively.

[0040] For example, in the silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 1.5%, 84%, 11.3% and 3.2% respectively.

[0041] For example, in the silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 0.8%, 76%, 21.2% and 2% respectively.

[0042] For example, in the silver paste, the mass fractions of the organic additive, silver powder, organic binder and doped glass powder are 1.1%, 79%, 17% and 2.9% respectively.

[0043] Optionally, in one embodiment, the silver powder includes micron-sized spherical silver powder and nano-sized spherical silver powder. Since there are gaps between the micron-sized silver powder and the silver powder, the nano-sized spherical silver powder can just fill and penetrate into the gaps between the micron-sized silver powder.

[0044] Optionally, in a specific embodiment, the silver powder includes 85-90% by mass of micron-sized spherical silver powder and 10-15% by mass of nano-sized spherical silver powder.

[0045] Optionally, in a specific embodiment, the silver powder includes micron-sized spherical silver powder with a purity of 3 9s and a mass fraction of 85-90% and a D50 of 5-6 μm, and nano-sized spherical silver powder with a purity of 3 9s and a mass fraction of 10-15%.

[0046] Optionally, in one embodiment, the organic auxiliary agent includes one or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, lauryl alcohol phosphate mixture, Digo 655, and BYKl09.

[0047] In the N-type IBC battery negative electrode grid line silver paste provided in an embodiment of the present invention, the above-mentioned organic binder includes a polymer resin and an organic solvent; wherein the polymer resin is dissolved in the organic solvent, so that the organic solvent can be used as an organic binder, that is, the paste plays a role of bonding powder after drying.

[0048] Optionally, in one embodiment, the mass fraction of the high molecular weight polymer in the organic binder is 10-15%; the mass fraction of the organic solvent in the organic binder is 85-90%.

[0049] Optionally, in some embodiments, the mass fraction of the high molecular polymer in the organic binder is 12-13%; the mass fraction of the organic solvent in the organic binder is 87-88%.

[0050] Optionally, in one embodiment, the high molecular weight polymer is one or more of ethyl cellulose-N20, ethyl cellulose N-50, and ethyl cellulose-N100;

[0051] The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0052] The embodiment of the present invention also provides a method for preparing silver paste for negative electrode grid line of N-type IBC battery, wherein: Figure 1 As shown, it includes steps 101 to 102:

[0053] Step 101: Mix silver powder, organic binder and doped glass powder to obtain a mixture; wherein the doping elements of the doped glass powder are antimony, tellurium and tungsten;

[0054] Step 102: Grind the mixture, add an organic additive, and obtain a silver paste for negative electrode grid lines of an N-type IBC battery.

[0055] In the above step 101, 76-84% of silver powder, 11.3-21.2% of organic binder, and 2-3.2% of doped glass powder accounting for the total mass of the raw materials are weighed and mixed, and dispersed by a disperser to obtain the above mixture.

[0056] Optionally, in one embodiment, in the above step 101, the organic binder and nano-scale spherical silver powder are first mixed and dispersed using a disperser, and then micron-scale spherical silver powder and doped glass powder are added, dispersed again using a disperser, and then ground to obtain the above mixture.

[0057] In the above step 102, the above mixture is ground and then an organic additive accounting for 0.8-1.5% of the total mass of the raw materials is added. After high-speed dispersion, a silver paste is obtained that can be used to form a negative electrode grid line in contact with the N-type area on the back of the IBC battery and can significantly improve the photoelectric conversion efficiency of the battery.

[0058] In the embodiment of the present invention, by doping antimony, tellurium and tungsten elements into the glass powder, antimony and phosphorus are both pentavalent elements, and the doping of the N region can be increased; and tellurium and tungsten have a silver-dissolving effect, which can reduce the contact resistivity of the silver grid line and improve the fill factor, thereby improving the photoelectric conversion efficiency of the battery; thereby solving the problem that the existing N-type IBC battery cannot form an n+ region, resulting in poor photoelectric conversion efficiency of the N-type IBC battery.

[0059] Optionally, in the preparation method provided in an embodiment of the present invention, the doped glass powder includes 10-25% Bi2O3, 6-8% Al2O3, 8-15% SiO2, 5-15% ZnO, 25-40% Sb2O3, 5-12% TiO2, 5-12% WO2, 5-10% MgO and 15-20% TeO3 in mass percentage.

[0060] Optionally, in the preparation method provided in an embodiment of the present invention, D50 of the doped glass powder is 1.5-2 μm.

[0061] Optionally, in the preparation method provided in an embodiment of the present invention, the organic auxiliary agent includes three or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate mixture.

[0062] Optionally, in the preparation method provided in the embodiment of the present invention, the organic binder comprises a high molecular polymer resin and an organic solvent;

[0063] The mass fraction of the high molecular weight polymer in the organic binder is 10 to 15%;

[0064] The mass fraction of the organic solvent in the organic binder is 85-90%.

[0065] Optionally, in the preparation method provided in the embodiment of the present invention, the high molecular polymer is resin-50;

[0066] The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0067] Optionally, in the preparation method provided in the embodiment of the present invention, the silver powder includes micron-spherical silver powder and nano-spherical silver powder.

[0068] The present invention also provides a method for preparing an N-type IBC battery, wherein: Figure 2 As shown, it includes steps 201 to 203:

[0069] Step 201, after forming an n-type doped region and a p-type doped region arranged in an interdigitated manner on the back side of an N-type silicon wafer, a passivation layer is formed on the surface of the n-type doped region and the p-type doped region;

[0070] Step 202: forming an opening in communication with the p-type doping region in the first region of the passivation layer, and printing aluminum paste at the opening, and printing silver paste in the second region of the passivation layer; the projection of the first region is within the range of the p-type doping region, and the projection of the second region is within the range of the n-type doping region; wherein the silver paste comprises an organic additive, silver powder, an organic adhesive and doped glass powder, and the doping elements of the doped glass powder are antimony, tellurium and tungsten;

[0071] Step 203 , high-temperature sintering is performed on the N-type silicon wafer with aluminum paste printed in the opening and silver paste printed in the second area to obtain an N-type IBC battery.

[0072] In the above step 201, the N-type silicon wafer is first subjected to alkali texturing, and then an n-type doped region and a p-type doped region arranged in a finger-like manner are formed on the back of the silicon wafer, and then a silicon oxide layer and / or a silicon nitride layer is deposited to cover the entire back of the silicon wafer as the above-mentioned passivation layer.

[0073] Among them, the P-type doped area is formed by boron diffusion and laser SE process on N-type silicon wafer to further reduce metal recombination and increase the opening voltage.

[0074] In the above step 202, a silicon wafer after forming a passivation layer is taken, and an opening connected to the p-type doped region is formed in the first region of the passivation layer by laser grooving or the like, and the projection of the first region is within the range of the p-type doped region. Then, aluminum paste is screen-printed at the opening to form a positive electrode grid line that is conductive to the p-type doped region, wherein the aluminum paste can be a traditional aluminum paste. At the same time, the silver paste also needs to be printed in the second region of the back passivation layer, and the projection of the second region is within the range of the n-type doped region to form a negative electrode grid line spaced apart from the positive electrode grid line.

[0075] In the above step 203, because the silver powder has a burn-through property, the above silver paste is directly printed on the passivation layer area above the n-type doped area and then sintered at a high temperature, so as to burn through the passivation layer and form a negative electrode grid line in contact with the n-type doped area; at the same time, because the glass powder is doped with antimony, tellurium and tungsten elements, antimony and phosphorus are both pentavalent elements, which can increase the doping of the N region; and tellurium and tungsten have a silver-dissolving effect, which can reduce the contact resistivity of the silver grid line and improve the fill factor, thereby improving the photoelectric conversion efficiency of the battery.

[0076] The present invention is described in detail below by way of examples.

[0077] Example 1

[0078] (1) providing a silver paste: the silver paste is composed of 1.2 parts of an organic additive, 80 parts of silver powder, 16.8 parts of an organic binder and 2 parts of a doped glass powder, by weight;

[0079] The organic additives include three of silane coupling agents, silicone oil, and a mixture of lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 9s and a mass fraction of 90%, and nano-spherical silver powder with a purity of 3 9s and a mass fraction of 10%; the organic binder includes resin-50 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent includes benzyl alcohol, diethyl phthalate, pinene alcohol, butyl carbitol, butyl carbitol acetate, and tributyl citrate;

[0080] The doped glass powder is obtained by sintering and crushing 14% Bi2O3, 6% Al2O3, 6% SiO2, 6% ZnO, 30% Sb2O3, 5% TiO2, 10% WO2, 8% MgO and 15% TeO3 by mass percentage.

[0081] (2) After forming a silicon oxide layer and a polysilicon layer on the back side of an N-type silicon wafer with a size of 182 mm × 182 mm, the back side polysilicon layer is subjected to boron diffusion and laser SE treatment;

[0082] (3) laser grooving the back side of the phosphorus-doped N-type silicon wafer to form interdigitated n-type doped regions and p-type doped regions, and removing the front polysilicon layer;

[0083] (4) after removing the front polysilicon layer and sequentially forming a double-sided aluminum oxide layer, a front silicon nitride layer, and a back silicon nitride layer, laser grooving is performed on the back silicon nitride layer opposite to the p-type doped region to form an opening, the aluminum paste is printed at the opening using a 480-mesh screen, and the silver paste is printed on the back silicon nitride layer opposite to the n-type doped region;

[0084] (5) The silicon wafer is sintered at a high temperature in a sintering furnace, with a peak sintering temperature of 772° C., to produce an N-type IBC battery.

[0085] Example 2

[0086] The difference between Example 2 and Example 1 is that in step (1), the doped glass powder includes 10% Bi2O3, 8% Al2O3, 8% SiO2, 7% ZnO, 25% Sb2O3, 12% TiO2, 5% WO2, 10% MgO and 15% TeO3 in mass percentage.

[0087] Example 3

[0088] The difference between Example 3 and Example 1 is that in step (1), the doped glass powder includes 10% Bi2O3, 8% Al2O3, 8% SiO2, 7% ZnO, 25% Sb2O3, 5% TiO2, 12% WO2, 5% MgO and 20% TeO3 in mass percentage.

[0089] Example 4

[0090] The difference between Example 4 and Example 1 is that in step (1), the doped glass powder includes 10% Bi2O3, 8% Al2O3, 8% SiO2, 7% ZnO, 25% Sb2O3, 7% TiO2, 8% WO2, 7% MgO and 18% TeO3 in mass percentage.

[0091] Example 5

[0092] The difference between Example 5 and Example 1 is that in step (1), the silver paste consists of 0.8 parts of organic additives, 84 parts of silver powder, 12 parts of organic binder and 3.2 parts of doped glass powder, by mass.

[0093] Example 6

[0094] The difference between Example 6 and Example 1 is that in step (1), the silver paste consists of 1.5 parts of organic additives, 76 parts of silver powder, 20.5 parts of organic binder and 2 parts of doped glass powder, by mass.

[0095] Comparative Example 1

[0096] The difference between Comparative Example 1 and Example 1 is that in step (1), the silver paste consists of 1.2 parts of organic additives, 80 parts of silver powder, 16.8 parts of organic binder and 2 parts of glass powder, and the glass powder includes 24% Bi2O3, 22% Al2O3, 10% SiO2, 16% ZnO, 15% TiO2 and 13% MgO in mass percentage.

[0097] The electrical performance of the N-type IBC batteries prepared in the above embodiments and comparative examples was tested, and the results are shown in Table 1 below:

[0098] Table 1

[0099]

[0100] By comparing Examples 1 to 6 with Comparative Example 1, it can be seen that by doping antimony, tellurium and tungsten elements into the glass powder, the contact resistivity of the silver grid line can be reduced, the fill factor can be increased, and the photoelectric conversion efficiency of the battery can be improved. The efficiency of the battery is increased by 0.08%.

[0101] In summary, in this embodiment, by doping antimony, tellurium and tungsten elements into the glass powder, antimony and phosphorus are both pentavalent elements, and the doping of the N region can be increased; and tellurium and tungsten have a silver-dissolving effect, which can reduce the contact resistivity of the silver grid line and improve the fill factor, thereby improving the photoelectric conversion efficiency of the battery; thereby solving the problem that the existing N-type IBC battery cannot form an n+ region, resulting in poor photoelectric conversion efficiency of the N-type IBC battery.

[0102] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0103] The above is a detailed introduction to an N-type IBC battery negative electrode grid line silver paste, an N-type IBC battery and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for a general technician in this field, according to the idea of ​​the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A silver paste for negative gate lines of an N-type IBC battery, characterized in that: The components constituting the silver paste include organic additives, silver powder, organic adhesive and doped glass powder, and the doped elements of the doped glass powder are antimony, tellurium and tungsten.

2. The silver paste according to claim 1, characterized in that The mass fractions of the organic auxiliary agent, silver powder, organic adhesive and doped glass powder are 0.8-1.5%, 76-84%, 11.3-21.2% and 2-3.2% respectively.

3. The silver paste according to claim 1, characterized in that The doped glass powder includes 10-25% Bi2O3, 6-8% Al2O3, 8-15% SiO2, 5-15% ZnO, 25-40% Sb2O3, 5-12% TiO2, 5-12% WO2, 5-10% MgO and 15-20% TeO3 in mass percentage.

4. The silver paste according to claim 1, characterized in that The D50 of the doped glass powder is 1.5-2 μm.

5. The silver paste according to claim 1, characterized in that The organic auxiliary agent includes three or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate mixture.

6. The silver paste according to claim 5, characterized in that The organic binder includes a high molecular polymer resin and an organic solvent; The mass fraction of the high molecular weight polymer in the organic binder is 10 to 15%; The mass fraction of the organic solvent in the organic binder is 85-90%.

7. The silver paste according to claim 6, characterized in that The high molecular polymer is resin-50; The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

8. The silver paste according to claim 1, characterized in that The silver powder includes micron-spherical silver powder and nano-spherical silver powder.

9. A method for preparing an N-type IBC battery, characterized in that: include: After forming an n-type doped region and a p-type doped region arranged in an interdigitated manner on the back of an N-type silicon wafer, a passivation layer is formed on the surface of the n-type doped region and the p-type doped region; An opening connected to the p-type doping region is formed in the first region of the passivation layer, and aluminum paste is printed at the opening, and silver paste is printed in the second region of the passivation layer; the projection of the first region is within the range of the p-type doping region, and the projection of the second region is within the range of the n-type doping region; wherein the silver paste comprises an organic additive, silver powder, an organic adhesive and doped glass powder, and the doping elements of the doped glass powder are antimony, tellurium and tungsten; The N-type silicon wafer with aluminum paste printed in the opening and silver paste printed in the second area is sintered at high temperature to obtain an N-type IBC battery.

10. An N-type IBC battery, characterized in that: The method according to claim 9 is used to prepare the product.

Citation Information

Patent Citations

  • Telluride doped high tension solar energy cell front side silver slurry and preparation method thereof

    CN108511106A

  • Front-side conductive paste of crystalline silicon solar cell, preparation method thereof, and solar cell

    CN110603606A

  • Titanium and calcium doped PERC solar cell front silver paste and preparation method thereof

    CN113257454A

  • N-type TOPCon battery back polishing silver paste and preparation method and application thereof

    CN114373568A